Impact of outdoor units of heat pumps and air conditioning equipment on ambient air - Gellai, László; Géczi, Gábor (Journal of Central European Green Innovation, 2025)
Heat pumps (HPs) and air conditioning (AC) systems have become key technologies in reducing energy consumption and greenhouse gas emissions. Their efficiency and comfort-related benefits have been widely studied; however, the environmental impact of their outdoor units—particularly their effects on ambient air quality—has received less attention. The fans of outdoor units generate local airflows that can influence both temperature distribution and the concentration of air pollutants, primarily particulate matter (PM). We conducted long-term observations of air quality on balconies connected to dormitory rooms, focusing mainly on PM concentration. In cases where the outdoor unit of the air conditioner was installed on the balcony, a measurable “cleaning effect” was observed. Depending on the operating mode of the unit, its impact on the ambient temperature was also detectable.
Keywords: outdoor unit; fan; air quality; particulate matter (PM)